Peningkatan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Melalui Senam Irama - Siti Mariam Mariam; Sadaruddin Sadaruddin; Ashar Ashar (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This research is motivated by the low gross motor skills of children aged 5-6 years at Batara Bira Kindergarten, Makassar, which is attributed to the dominance of cognitive academic activities and a lack of programmed physical stimulation. Initial observations revealed that 63% of the children (7 out of 11) exhibited passive behavior and faced serious challenges regarding coordination and body balance. This study aims to improve children's gross motor skills through the application of a modified rhythmic gymnastics method. The research method employed is Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles. The research subjects consisted of 11 students from Group B. Data were collected through participatory observation using a gross motor development checklist instrument, which includes indicators of active participation, controlled movement, and anticipatory ability. Data analysis was performed using a comparative descriptive technique to compare achievements across cycles. The results indicated a significant improvement in children's gross motor skills. In the pre-action stage, the average classical achievement was only 28% (categorized as